2021
DOI: 10.1053/j.gastro.2020.12.024
|View full text |Cite
|
Sign up to set email alerts
|

An International Multicenter Real-Life Prospective Study of Electronic Chromoendoscopy Score PICaSSO in Ulcerative Colitis

Abstract: BACKGROUND & AIMS: Endoscopic and histologic remission are important goals in the treatment of ulcerative colitis (UC). We investigated the correlation of the recently developed Paddington International Virtual ChromoendoScopy ScOre (PICaSSO) and other established endoscopic scores against multiple histological indices and prospectively assessed outcomes. METHODS: In this prospective multicenter international study, inflammatory activity was assessed with high-definition and virtual chromoendoscopy in the rect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 51 publications
(114 citation statements)
references
References 39 publications
6
97
1
1
Order By: Relevance
“…We have recently reported that, even with high definition and electronic chromoendoscopy, endoscopic remission and histologic remission equally predict clinical outcomes at 1 year. 36 Thus endoscopy is getting closer to histology and AI might enable efficient use of endocytoscopy with minimal training and time.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported that, even with high definition and electronic chromoendoscopy, endoscopic remission and histologic remission equally predict clinical outcomes at 1 year. 36 Thus endoscopy is getting closer to histology and AI might enable efficient use of endocytoscopy with minimal training and time.…”
Section: Discussionmentioning
confidence: 99%
“…Colonic mucosa was inspected, and precise assessments of inflammatory activity took place using high-definition white light endoscopy and Virtual Electronic Chromoendoscopy (Optical Enhancement iScan mode/Narrow-Band Imaging (NBI)) with and without magnification ( Fig 1A–1C ). Inflammatory activity was graded using the MES [ 10 ], Ulcerative Colitis Endoscopic Index of Severity (UCEIS) [ 16 ] and the PICaSSO score [ 7 , 9 ] in patients with UC and SES-CD in patients with CD [ 17 ]. Using these advanced endoscopic technologies and novel scores such as the PICaSSO score [ 9 ], targeted biopsies of inflamed/healed areas, which best reflected the overall inflammatory activity irrespective of colonic segment, were taken for ex vivo RS analysis and histological analysis at the same site.…”
Section: Methodsmentioning
confidence: 99%
“…Response to biological therapy was described as a reduction in endoscopic inflammatory activity score and in histological inflammatory score. The following stringent criteria were used to define patients with MH: MES [ 10 ] ≤1, UCEIS (Ulcerative colitis endoscopic index of severity) score [ 16 ] ≤1, PICaSSO score [ 7 , 9 ] ≤3 in addition to histological remission defined as RHI (Robarts Histological Index) score ≤3 without neutrophils in the epithelium and Lamina Propria [ 18 ] for UC. The following criteria were used to define MH in CD patients: SES-CD (Simple endoscopic score for Crohn’s disease) [ 17 ] ≤2 and a modified Riley score 0 in CD [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ausgerichtet. Zur Differenzierung innerhalb der weniger schweren Stadien, also v. a. zur differenzierten Betrachtung einer Mukosaheilung, wurde der PICASSO-Score mithilfe der virtuellen Chromoendoskopie validiert, der reproduzierbar eine Unterscheidung geringradiger entzündlicher Veränderungen von einer vollständigen Mukosaheilung zulässt [83,84]. Insgesamt wurde die Methodologie zur Erstellung neuer Messinstrumente zur Erfassung der endoskopischen Krankheitsaktivität bei C. ulcerosa in den letzten Jahren erheblich verfeinert.…”
Section: Uccisunclassified